Analysis of Discounts and Consumer Perceptions as Driving Factors of Purchase Intention for Electric Motorcycles in Kudus Regency - Milad Nufal Akbar; Darsin Dasin (Dinasti Publisher, 2026)
The increase in electric motorcycle sales in Indonesia reflects market conditions that are dynamic and unstable. However, following the withdrawal of government subsidies in September 2024, sales experienced a significant decline. This study aims to analyze the influence of discounts and consumer perceptions on purchase intention toward electric motorcycles, particularly in the Kudus region. The research adopts an explanatory quantitative approach using a nonprobability sampling technique involving 200 respondents from two showrooms of the UWF and UM brands. Data were collected through interviews with 100 walk-in respondents and from 100 registered respondents by distributing online questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS. The findings indicate that discounts and consumer perceptions have a significant effect on purchase intention, with discounts exerting a more dominant influence than perceptions. Furthermore, price perception emerges as the strongest factor compared to value and risk perceptions. Therefore, more targeted promotional strategies and improvements in the quality of sales human resources are required to support the growth of the electric motorcycle market